Strategi Pengembangan Pemasaran UKM Pengrajin Sepatu Sandal - Sulistiono, Sulistiono; Mubarak, Mumuh Mulyana (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2012)
Small and medium Enterprisis (SMEs) have significant role in national economic development. The problems of this research are (1) marketing strategies which has been impemented by sandal shoes craftman in Ciomas Bogor, (2) strengths, weaknesses, opportunities, and threats faced by sandal shoes craftman in Ciomas Bogor, (3) whatâs the next marketing strategy which is be able to make sandal shoes selling increases. The results of this research are (1) The internal factors: strength quadrant embraces qualified product, competitive price, and unique sandal shoes; weaknesses quadrant encompasses unmanaged financial management, uneffective raw inventary management, supervision of production process and its quality is not good enough, the place to work is not comfortable enough, minimum technology, and the production cost calculation isnât accurate; (2) The external factors: opportunity quadrant embraces the availability of human resources, public knows the products, the location is near to the supplier, conducting centralized marketing system, the sales can be run in marketable place with a lot of relationships. The development strategies which can be done are increasing sandal shoes models, optimizing marketing channels or networks, expanding marketing relationship networks, using website or email as means of promotin and marketing (developing E-Commerce), allocating funds for production technology, cooperating with the others to provide raw materials and working capital, and working together to build collective power thatâs able to eliminate the weaknesses.